Inhibition of malaria parasite growth by quinomycin A and its derivatives through DNA-intercalating activity. Issue 4 (3rd April 2015) - Hayase, Hiroki; Watanabe, Nobumoto; Lim, Chung Liang; Nogawa, Toshihiko; Komatsuya, Keisuke; Kita, Kiyoshi; Osada, Hiroyuki
Abstract: Quinomycin A and its derivatives were identified as potent antimalarial ( Plasmodium falciparum ) agents in a screen of the RIKEN NPDepo chemical library. IC50 values of quinomycin A and UK-63, 598 were approximately 100 times lower than that of the antimalarial drug chloroquine. This activity was mitigated by the addition of plasmid DNA, suggesting that these compounds act against parasites by intercalating into their DNA.